La città in campagna e la campagna in città. Architettura e natura. Atti del IV Convegno diffuso internazionale San Venanzo, Terni, 13-17 settembre 2016 - Damiano, Stefano (Paesaggi: città, natura, infrastrutture - Open Access, 2017)
The volume collects the proceedings of the IV international widespread convention held in September 2016 in San Venanzo (Italy) within the event "Architecture and Nature - Simonetta Bastelli Award". It is divided into as many sections as were the days and the different topics addressed: "The network/The systems", "City in the Countryside", "Countryside in the City", in addition to the lectio magistralis of the Portuguese landscape designer João Ferreira Nunes and the conference of Perry Maas of the Rotterdam WEST 8 design team - Urban Design & Landscape Architecture. The intent of the publication, as well as of the convention, is to understand the relationships and interdependencies existing between the city and the countryside in intlight of a new model of sustainable development.